PEMANFAATAN CRITICAL LEGAL STUDIES (CLS) DALAM PEMBENTUKAN PERATURAN DAERAH - Erfina Fuadatul Khilmi (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2019)
Critical Legal Studies thinking is important to understand social reality and legal order to form commitment and legal unification based on legal theory based on social praxis to reconstruct the unequal social structure in the formation of Regional Regulations. The main use of CLS legal theory is its criticality of doctrine and legal system as well as values ??and commitment to seek a transformative legal and social potential based on social praxis, thus influencing the formation of regional regulations in contributing to stability and perpetuating the existing social order. The weakness of critical legal thinking (CLS) is that if the use of this criticism is trapped in an endless mainstream, then this criticism is only limited to discourse and will always be marginalized on the edge of the social system and considered a strange creature that must be removed. The relevance of CLS legal theory lies in the objective criticism and legal formalism related to Article 14 UUUP3 regarding Regional Regulations as regional autonomy instruments which is ambiguous because the concept of implementing regional autonomy is generalized by legal positivism through tiered legal rules. This is very unequal in the formation of regional regulations in the empirical realm which is the result of a process that is loaded with various contents, values, and interests of the actors/political elites involved in it.